Protocells: Modular Mesoporous Silica Nanoparticle‐Supported Lipid Bilayers for Drug Delivery. Issue 16 (18th January 2016) - Butler, Kimberly S.; Durfee, Paul N.; Theron, Christophe; Ashley, Carlee E.; Carnes, Eric C.; Brinker, C. Jeffrey
Abstract : Mesoporous silica nanoparticle‐supported lipid bilayers, termed 'protocells, ' represent a potentially transformative class of therapeutic and theranostic delivery vehicle. The field of targeted drug delivery poses considerable challenges that cannot be addressed with a single 'magic bullet'. Consequently, the protocell has been designed as a modular platform composed of interchangeable biocompatible components. The mesoporous silica core has variable size and shape to direct biodistribution and a controlled pore size and surface chemistry to accommodate diverse cargo. The encapsulating supported lipid bilayer can be modified with targeting and trafficking ligands as well as polyethylene glycol (PEG) to effect selective binding, endosomal escape of cargo, drug efflux prevention, and potent therapeutic delivery, while maintaining in vivo colloidal stability. This review describes the individual components of the platform, including the mesoporous silica nanoparticle core and supported lipid bilayer, their assembly (by multiple techniques) into a protocell, and the combined, often synergistic, performance of the protocell based on in vitro and in vivo studies, including the assessment of biocompatibility and toxicity. In closing, the many emerging variations of the protocell theme and the future directions for protocell research are commented on. Abstract : Targeted drug delivery poses challenges that cannot be addressed with a single 'magic bullet'. Consequently, the protocell has been designed as a modular platform composed of interchangeable biocompatible components. This review describes the features and synthesis of the individual components, their assembly into protocells, the performance of the protocell in vitro and in vivo, and goals for its future development.